Scales for the Evaluation of End-of-Life Care in Advanced Dementia: Sensitivity to Change - Kiely, Dan K. (2012)
The paucity of valid and reliable instruments designed to measure end-of-life experiences limits advanced dementia and palliative care research. Two end-of-life in dementia (EOLD) scales that evaluate the experiences of severely cognitively impaired persons and their health care proxies (HCP) have been developed: 1) symptom management (SM) and 2) satisfaction with care (SWC). The study objective was to examine the sensitivity of the EOLD scales to detect significant differences in clinically relevant outcomes in nursing home residents with advanced dementia. The SM-EOLD scale was sensitive to detecting changes in comfort among residents with pneumonia, pain, dyspnea, and receiving burdensome interventions. The SWC-EOLD scale was sensitive to detecting changes in HCP satisfaction with the care of residents when addressing whether the health care provider spent > 15 minutes discussing the resident’s advanced care planning, whether the physician counseled about the resident’s live expectancy, whether resident resided in a special care unit and whether the physician counseled possible resident health problems. This study extends the psychometric properties of the EOLD scales by showing the sensitivity to clinically meaningful change in these scales to specific outcomes related to end-of-life care and quality of life among residents with end-stage advanced dementia and their HCPs.